"Urban Nomad": Spatiality, Exile, and Political Engagement in Julio Cortázar's "Press Clippings" (1980). Issue 1 (2nd January 2022) - Kenny, Ivan
Abstract : This article examines spatiality, exile, and political engagement in the short story "Press Clippings" ("Recortes de prensa") (1980) by Julio Cortázar. Its aim is to contribute to a new understanding of how spatial metaphors operate in Cortázar's oeuvre, a dimension often obscured by a critical focus on temporality. While the question of spatiality in his works has received some scholarly attention, an in-depth analysis of the connections between narrative space, exile, and political critique in this story remains to be undertaken. Drawing on Said's ideas on the spatio-cultural aspects of exile (2000), and Deleuze and Guattari's theories on smooth and striated space (1987), I argue that the spatial metaphors in the narrative, such as the protagonist's "nomadic" movement through Paris, examine political engagement through art from a position in exile and illustrate how an exile's experience of the homeland is predominantly mediated through fragments of cultural texts. The analysis demonstrates how Cortázar uses literary space in the story to critique state terror in Argentina during the "Dirty War".